Safety Critical Components in Relation to Railway Vehicles Maintenance (Current Problems in Rail Vehicles, 2021)
Safety critical components (SCC) are a key element of the new EU Implementing Regulation 2019/779, which defines the responsibilities of entities in charge of maintenance of all types of railway vehicles. They are essential for assessing the risks associated with the operation and maintenance of railway vehicles and which directly affect railway safety. The paper presents the current situation in Europe in this area, pointing out that a methodology for determining the SCC has not yet been established.
Keywords: maintenance; safety critical components; EU regulation